Доказать тождество:
tg x tg (пи/3 - x)tg (пи/3 + x) = tg 3x
tgx•tg(pi/3-x)•tg(pi/3+x)=tg3x tgx•[(tg(pi/3)-tgx)/(1+tg(pi/3)•tgx)]•[(tg(pi/3)+tgx)/(1-tg(pi/3)•tgx)]=tg3x tgx•(√3-tgx)•(√3+tgx)/(1-√3tgx)•(1+√3tgx)=tg3x tgx•(3-tg²x)/(1-3tg²x)=tg3x (3tgx-tg³x)/(1-3tg²x)=tg3x tg3x=tg3x ✓
решение:
tgx*tg(pi/3-x)•tg(pi/3+x)=tg3x tgx*[(tg(pi/3)-tgx)/(1+tg(pi/3)•tgx)]•[(tg(pi/3)+tgx)/(1-tg(pi/3)•tgx)]=tg3x tgх*(√3-tgx)•(√3+tgx)/(1-√3tgx)•(1+√3tgx)=tg3x tgx*3-tg²x)/(1-3tg²x)=tg3x (3tgx-tg³x)/(1-3tg²x)=tg3x tg3x=tg3x